Being numerous : poetry and the ground of social life - Izenberg, Oren (20/21 (Princeton, N.J.), 2011)
"Because I am not silent," George Oppen wrote, "the poems are bad." What does it mean for the goodness of an art to depend upon its disappearance? In Being Numerous, Oren Izenberg offers a new way to understand the divisions that organize twentieth-century poetry. He argues that the most important conflict is not between styles or aesthetic politics, but between poets who seek to preserve or produce the incommensurable particularity of experience by making powerful objects, and poets whose radical commitment to abstract personhood seems altogether incompatible with experience--and with poems. Reading across the apparent gulf that separates traditional and avant-garde poets, Izenberg reveals the common philosophical urgency that lies behind diverse forms of poetic difficulty--from Yeats's esoteric symbolism and Oppen's minimalism and silence to O'Hara's joyful slightness and the Language poets' rejection of traditional aesthetic satisfactions. For these poets, what begins as a practical question about the conduct of literary life--what distinguishes a poet or group of poets?--ends up as an ontological inquiry about social life: What is a person and how is a community possible? In the face of the violence and dislocation of the twentieth century, these poets resist their will to mastery, shy away from the sensual richness of their strongest work, and undermine the particularity of their imaginative and moral visions--all in an effort to allow personhood itself to emerge as an undeniable fact making an unrefusable claim. --From publisher's description